Determination of Polyphenol Compounds in Clinacanthus nutans and Their Potential as Antioxidants - Widodo, Nashi; Salma Wahid Marseti; Yuslinda Annisa; Fairuz Sarah Kamila; Rosyadah, Nuraini; Rifa’i, Muhaimin (Biotropika: Journal of Tropical Biology, 2025)
Free radicals can cause oxidative damage if they are produced in excess amounts in the body. To prevent this, the work of endogenous antioxidants needs to be supported by safe and effective exogenous antioxidants. Clinacanthus nutans is one of the sources of natural polyphenol compounds that have the potential to be used as free radical-scavenging agents. The study began with the extraction of C. nutans simplicia with microwave assisted extraction (MAE) using a 96% ethanol solvent. The amounts of phenols and flavonoids in the extract was then measured using the Folin-Ciocalteu and aluminium chloride techniques, and their antioxidant activity was assessed using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) scavenging assays. Based on the results of the study, it is known that C. nutans ethanolic extract contains higher flavonoids (238.29 ± 10.87 mgQE.g-1) than the total phenols (148.76 ± 1.26 mgGAE.g-1). This study also showed the potential of C. nutans extract as a free-radical scavenger with an IC50 from the NO-scavenging and DPPH assays of 28.37 ± 3.38 ppm and 117.84 ± 3.93 ppm, respectively. Despite the presence of high polyphenol content in the extract, its antioxidant activity was found to be relatively weak. Consequently, further study is necessary to ascertain the specific class of compounds responsible for its antioxidant activity and to assess its effectiveness.